Speaking Anxiety and The Development of Self-Confidence in Oral Communication Among Regional Language and Literature Education Students - Ilma Rahim; Ita Rosvita; Arif Hukmi (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze how speaking anxiety is experienced by university students and how they cope with it in the Abbicara (speaking skills) course of Makassar language learning. The study employed a qualitative descriptive approach. The participants were 36 students of the Regional Language and Literature Education Program (Class of 2025, Class C) who were enrolled in the Abbicara course. Data were collected through open-ended questionnaires and written reflections describing students’ experiences of speaking anxiety and their coping strategies. The data were analyzed through data reduction, thematic categorization, descriptive interpretation, and conclusion drawing. The findings show that students’ speaking anxiety appears in various interconnected forms, including linguistic insecurity, cognitive interference, physiological reactions, and social concerns during oral performance. Students cope with their anxiety through cognitive-affective and practical strategies such as strengthening self-confidence, reframing perceptions of mistakes, engaging in repeated practice, and managing physical tension. This study contributes novelty by focusing on speaking anxiety in a regional language context (Makassar), rather than in foreign language learning. The findings imply the need for structured confidence-building activities, gradual speaking exposure, and supportive feedback practices to foster psychologically safe and culturally responsive local language instruction.